A simplified model for the analysis of strain of beams, obtained test load bridges - Vargas-Padilla, Katherine (2014)
During the first live load test in bridges, performed in Costa Ricaon October 05th, 2012 that was managed by the multidisciplinary research project e-Bridge from the Technological Institute of Costa Rica,on the bridge over Purires River on National Route N° 2, lot of strain data obtain from flanges of the main steel beams of the structure,were mainly produced. The lack of an analysis mechanisms in this data meant an important challenge to assume. As a response to this need, a simplified model was proposed for calculating the total theoretical external moment over the structure for being compared with the internal experimental moment obtained from the proof test.From this comparison,it was possible to determinate thatthe deck acts in a non-composite action,that condition indicates that the deck and main steel beams do not work together for taking and distributing live load applied on the bridge. This situation forces tothe stresses over structurebeconcentrated on just a pair of elements meanwhile others do not receive the effect of loads applied, affecting the bridge global performance, so this method could detect easily one of the main structural problems on the bridge that otherwise require complex methods.